Drug‐phospholipid conjugate nano‐assembly for drug delivery - Ding Zhao; Yixiang Zhang; Fan Wang; Rames Kaewmanee; Wenguo Cui; Tianqi Wu; Yawei Du (Smart Medicine)
Abstract Phospholipid‐based liposomes are among the most successful nanodrug delivery systems in clinical use. However, these conventional liposomes present significant challenges including low drug‐loading capacity and issues with drug leakage. Drug‐phospholipid conjugates (DPCs) and their assemblies offer a promising strategy for addressing these limitations. In this review, we summarize recent advances in the design, synthesis, and application of DPCs for drug delivery. We begin by discussing the chemical backbone structures and various design strategies such as phosphate head embedding and mono‐/bis‐embedding in the sn‐1/sn‐2 positions. Furthermore, we highlight stimulus‐responsive designs of DPCs and their applications in treating diseases such as cancer, inflammation, and malaria. Lastly, we explore future directions for DPCs development and their potential applications in drug delivery.